2007
DOI: 10.3114/sim.2007.59.07
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Aspergillus species in some important agricultural products

Abstract: The genus Aspergillus is one of the most important filamentous fungal genera. Aspergillus species are used in the fermentation industry, but they are also responsible of various plant and food secondary rot, with the consequence of possible accumulation of mycotoxins. The aflatoxin producing A. flavus and A. parasiticus, and ochratoxinogenic A. niger, A. ochraceus and A. carbonarius species are frequently encountered in agricultural products. Studies on the biodiversity of toxigenic Aspergillus species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
199
2
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(233 citation statements)
references
References 63 publications
5
199
2
17
Order By: Relevance
“…Rhizopus stolonifer is the common black bread mould, which is also responsible for the post-harvest decay of a wide range of fruits, including strawberries and stone fruits (Pitt & Hocking, 1999). In addition, various species of the genus Aspergillus pose a threat to the food industry as they contaminate agricultural products during pre-harvest, harvest, processing and storage, and most notably produce aflatoxins and ochratoxin A (Perrone et al, 2007). Aspergillus fumigatus is of particular concern as it is the most common aetiological agent of invasive human aspergillosis, predominantly affecting immunocompromised individuals (Dagenais & Keller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopus stolonifer is the common black bread mould, which is also responsible for the post-harvest decay of a wide range of fruits, including strawberries and stone fruits (Pitt & Hocking, 1999). In addition, various species of the genus Aspergillus pose a threat to the food industry as they contaminate agricultural products during pre-harvest, harvest, processing and storage, and most notably produce aflatoxins and ochratoxin A (Perrone et al, 2007). Aspergillus fumigatus is of particular concern as it is the most common aetiological agent of invasive human aspergillosis, predominantly affecting immunocompromised individuals (Dagenais & Keller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These strains can be classified as atypical A. flavus (TRAN-DINH et al, 1999;PILDAÍN et al, 2004;PERRONE et al, 2007). This strain isolated presents all macroscopic and microscopic morphological characteristics of A. flavus differentiating morphologically A. parasiticus (KLICH, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic studies of A. flavus showed that it consists of two subgroups (I and II) (TRAN-DINH et al, 1999). Most group I strains produced Aflatoxin B, and most group II strains produced both Aflatoxin B and Aflatoxin G (PILDAÍN et al 2004;PERRONE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It causes many diseases on plant because of its ability to produce hydrolytic and oxidative enzymes which could involve in breakdown of plant lignocellulos [24]. It is known as a main causative agent of black mold and rot disease on different fruits and vegetables also commonly used in food industry because of production of extracellular organic acids materials [24,23,22,27]. A. niger has been tagged with the generally recognized as safe status from the US Food and Drug Administration [25].…”
Section: Introductionmentioning
confidence: 99%